A T-resonator technique for aperture plane admittance parameters of electrically short RF monopoles - Kwinana, Phumezo M. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.